2019
DOI: 10.1016/j.marpolbul.2019.02.068
|View full text |Cite
|
Sign up to set email alerts
|

Characterising the deterioration of different plastics in air and seawater

Abstract: In situ studies of plastic deterioration can help us understand the longevity of macroplastic as well as the generation of microplastics in the environment. Photo-oxidation contributing to the generation of microplastics in the marine environment was explored using four types of plastic (polyethene, polystyrene, poly(ethylene terephthalate) and Biothene exposed in light and in shade, in both air and sea water. Metrics for deterioration were tensile extensibility and oxidation rate. Measurements were conducted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
20
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(27 citation statements)
references
References 37 publications
5
20
0
1
Order By: Relevance
“…Let us consider an elongated object with a Young modulus E ≈ 1 GPa and a diameter d ≈ 50 µm. These values are rather classical for plastic materials, as plastic films for example [57,58] which have a typical thickness of 50 µm. The turbulent flow near the ocean surface experienced by plastic debris is most of the time weakly turbulent, with turbulent dissipation rates of the order of ε ≈ 10 −6 − 10 −3 m 2 /s 3 caused by wind shear on the ocean surface [21].…”
Section: Application To Plastic Fragmentation In the Oceanmentioning
confidence: 99%
“…Let us consider an elongated object with a Young modulus E ≈ 1 GPa and a diameter d ≈ 50 µm. These values are rather classical for plastic materials, as plastic films for example [57,58] which have a typical thickness of 50 µm. The turbulent flow near the ocean surface experienced by plastic debris is most of the time weakly turbulent, with turbulent dissipation rates of the order of ε ≈ 10 −6 − 10 −3 m 2 /s 3 caused by wind shear on the ocean surface [21].…”
Section: Application To Plastic Fragmentation In the Oceanmentioning
confidence: 99%
“…These first few weeks of exposure were marked by the least amount of biofilm, and consequently, the greatest amount of UV transmittance, which would have facilitated photo-oxidation reactions. The role of photo-oxidation in the degradation of plastics has been previously noted in a study by Biber et al (2019) , who found that the deterioration of polyethylene, PET, PS, and Biothene® was faster in direct sunlight compared to shade, and in air compared to water. These results corroborate those of an earlier study by Pegram and Andrady (1989) , who found little evidence of weathering of polyethylene samples floating in seawater over an 8-week period, whereas those exposed to air nearly embrittled over the same period.…”
Section: Discussionmentioning
confidence: 59%
“…In the context of this study, the lowest rate of degradation was observed in open-air conditions for all four of the studied environments. Contrary to that of previous studies, the non-degradable plastic fragmented in open-air faster when compared to the marine environment [7], [17]. However, in these previous studies the impact of grazers was limited as the sampled products were shielded by dense mesh.…”
Section: Discussionmentioning
confidence: 71%